Management of confiscated goods and looted goods of the state at the Class I RUPBASAN Bengkulu: Pengelolaan Benda Sitaan dan Barang Rampasan Negara Pada Rupbasan Kelas I Bengkulu - Wijaya, Trio Sandra (Indonesian Journal of Police Studies, 2021)
In the existing legal system in Indonesia, goods and objects suspected of being evidence of a criminal act must be secured in order to carry out further investigations into the criminal acts committed. The existence of a house for storing state confiscated objects or abbreviated as Rupbasan is very important as a place to keep the evidence of the crime until the investigation is complete and the verdict has been issued for abandoning the crime. In this study, the author wanted to see how far the management of goods and looted and confiscated by the state in the Rupbasan Class I Bengkulu. This research was conducted using a qualitative method by conducting interview data collection techniques and field observations, and the data obtained were primary data and secondary data. The implementation of the management carried out at the Bengkulu Class I Rupbasan is technically not appropriate but procedurally it is in accordance with the decision of the Director General of Corrections Number: E1.35.PK.03.10 of 2002 concerning Implementation Guidelines and Technical Instructions for Management of State Confiscated Objects and State Confiscated Goods. As well as found obstacles in the implementation of the management of confiscated state goods and goods, these obstacles consist of internal and external. Internal barriers are limited human resources and inadequate facilities and infrastructure. Meanwhile, external obstacles, such as the existence of found objects that are not in the legal process at the Rupbasan and the number of objects and goods that have obtained legal decisions but are not immediately executed, resulting in accumulation in the Rupbasan.